2005
DOI: 10.1124/jpet.105.085217
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Profile of Ciclesonide, a Novel Corticosteroid for the Treatment of Asthma

Abstract: Ciclesonide is a novel, inhaled corticosteroid under development for the treatment of asthma. Ciclesonide is activated to desisobutyryl-ciclesonide (des-CIC) in the lungs to provide potent anti-inflammatory activity. The investigations herein compared the activity of ciclesonide with fluticasone in animal models to assess efficacy/potency as an airway anti-inflammatory and the comparative side effect potential to consider the therapeutic ratio of each compound. In radioligand binding assays, des-CIC and flutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
37
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 34 publications
(40 reference statements)
6
37
0
2
Order By: Relevance
“…An earlier study of INSs that used competition assay methodology reported a similar rank order of relative binding potency: mometasone furoate > fluticasone propionate > budesonide > triamcinolone acetonide > dexamethasone (15). Studies conducted before the development of mometasone furoate consistently described the same relative binding affinity order (15,(21)(22)(23)(24); the binding affinity of desciclesonide (the active metabolite of the prodrug ciclesonide) is slightly less than that of fluticasone propionate (7,19).…”
Section: Derendorf and Meltzermentioning
confidence: 79%
See 1 more Smart Citation
“…An earlier study of INSs that used competition assay methodology reported a similar rank order of relative binding potency: mometasone furoate > fluticasone propionate > budesonide > triamcinolone acetonide > dexamethasone (15). Studies conducted before the development of mometasone furoate consistently described the same relative binding affinity order (15,(21)(22)(23)(24); the binding affinity of desciclesonide (the active metabolite of the prodrug ciclesonide) is slightly less than that of fluticasone propionate (7,19).…”
Section: Derendorf and Meltzermentioning
confidence: 79%
“…lung/nasal tissue). Subsequent intracellular esterification of desciclesonide with endogenous fatty acids produces reversible lipid conjugates of des-ciclesonide that become a reservoir of the drug in the lung or nasal mucosa (7,8).…”
mentioning
confidence: 99%
“…Entretanto, mudanças no conteúdo mineral ósseo total em crianças tratadas com doses elevadas de DPB ou BUD ou PF foram recentemente documentadas durante tratamento por período de 12 meses 42,43 . Estudo experimental documentou a ausência de efeito sobre o metabolismo ósseo com ciclesonida, mesmo em doses elevadas 20 .…”
Section: Metabolismo óSseounclassified
“…42,43 An experimental assay has documented the absence of effect on bone metabolism with ciclesonide, even in elevated doses. 20 …”
Section: Clinical Efficacymentioning
confidence: 99%